A study of the relationship between the grades of BLIS students to their particular job choice in a library upon graduation - Ngo, Dexter M.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This study aims to determine whether grades in librarianship areas of specialization affect BLIS students' choice of career areas of specialization. The study is divided into two parts; students and Graduates. Students enrolled in the University of the Philippines Institute of Library Science during the 2nd semester of Academic Year2000-01 and recent graduates from the Institute will be used as respondents in this study. The research instrument used for the study is the questionnaire and the survey method. Chi-square tables were used to test the hypothesis stating that there exists a relationship between student's grade and his or her library job choice.
The findings in this study indicate that there is no relationship between a students' library job choice and his grades. Only two of the chi-square tables rejected this hypothesis. Information technology is the branch of library science that is the most sought after job of BLIS students today. The demand for cataloguing and classification practitioners in the job market today cannot be easily ignored, even though BLIS students do not think of it as a potential job in the future.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines, Institute of Library Science--Graduate students